Consumer Preference Analysis of Surabaya Residents towards UHT Milk Products Using Conjoint Analysis with Cluster Sampling Technique - Handy Wiranata; Yulistiani, Ratna (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2025)
Surabaya is one of the cities in East Java Province with a relatively high level of activity and birth rate. Along with the increasing population, the community's food needs have also risen, particularly in terms of their preferences for consuming UHT milk. Various factors, including flavour variants, price, packaging material, expiration date, nutritional content, and other attributes, influence consumer preferences for UHT milk. This study aims to identify the attributes with the highest importance values for consumers when selecting UHT milk products, as well as to determine consumer preferences regarding the attribute variables of UHT milk products. The attributes examined in this study include packaging material, flavor variants, price, expiration date, and nutritional content. The research was conducted using a survey method, with the number of respondents determined by Slovin’s formula, and respondent sampling was carried out using a cluster sampling technique. According to consumer preferences, the most preferred UHT milk product is packaged in cans, with a utility value of 0.167. The desired range for the price attribute, with a utility value of 0.220, is less than 5,000 IDR. Regarding flavor, the chocolate variant is most favored, with a utility value of 0.369. For expiration date, UHT milk with the longest shelf life of over 12 months (before opening) has a utility value of 0.060. Lastly, for nutritional content, high protein content is preferred with a utility value of 0.208. The best choice for UHT milk has the following features: it comes in a can, costs less than 5,000 IDR, is chocolate-flavored, has an expiration date of 6–12 months, and is lactose-free. Contribution to Sustainable Development Goals (SDGs):SDG 2 – Zero HungerSDG 3 – Good Health and Well-beingSDG 12 – Responsible Consumption and ProductionSDG 9 – Industry, Innovation, and Infrastructure